Development of Palm Sugar Business Based on Creative Economy in Cikadu Village - A, Faisal; R, Rini; Fakhri, Muhammad; M, Afta; S, Egi; N, Fikri; S M, Imelda; Hendi P; A, Rifa; H, Nissa; M, Zanet; Ghazali, Puspa Liza; Pratiwi, Anggia Suci; Hendrawan, Budi; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Palm sugar is an abundant natural resource in Cikadu Hamlet. Most of the people of Cikadu Hamlet only produce palm sugar, there is no development of palm sugar products which have great potential if they dare to start, because a market can be created. The method used for the development of the palm sugar business in Cikadu Hamlet is primary data, namely data obtained directly from informants. This study of the development strategy for the palm sugar processing industry uses a survey approach, in the form of direct observation. Collecting data in this study using literature study techniques, field observations, and interviews. Interviews were conducted with related parties. Based on research data that has been conducted by researchers, dried palm sugar brownies products can have good results in the market